Inter-Institutional Collaboration In Handling Asn Neutrality Violations In The 2024 Samarinda City Regional Head Elections - Yonlius, Aprilianus; Noor, Muhammad; Paselle, Enos (Journal of Law, Politic and Humanities, 2025)
This study aims to analyze collaboration between institutions in handling violations of the neutrality of State Civil Apparatus (ASN) in the 2024 Samarinda City Regional Head Election (Pilkada). Through a qualitative descriptive approach, this study highlights how the Election Supervisory Agency (Bawaslu), the Human Resources Development and Personnel Agency (BKPSDM), and the Samarinda City Inspectorate carry out synergy based on the principles of collaborative governance which include forums, transparency, goal management, compromise, communication, democracy and equality, as well as commitment and stamina. The results of the study show that collaboration between institutions has been running with a fairly good work structure and coordination, but still faces a number of challenges such as weak transparency between agencies, limited resources, minimal public participation, and potential conflicts of interest at the local level. These findings emphasize the importance of improving communication, improving regulations, and periodic evaluations to ensure that ASN neutrality is maintained and the democratic process runs professionally, transparently, and accountably.